Nonsurgical Management of a Papillary Fibroelastoma of the Aortic Valve - Antonino M. Grande; Nicoletta Castiglione; Adelaide Iervolino; Francesco Nappi; Antonio Fiore (Case Reports in Cardiology)
We report the case of a 63-year-old woman who had an incidental echocardiographic diagnosis of papillary fibroelastoma (PFE) of the right coronary cusp of the aortic valve. The patient was informed about the embolic risk due to the pedunculated mass located on the aortic valve but she refused the proposed surgical removal. She was followed up yearly, and each follow-up included an echocardiographic evaluation of the mass. The lady is taking lysine acetylsalycilate 160 mg daily, and after more than 19 years later, she does not complain any symptoms or complications as a result of possible embolic episodes. If on one hand, our report is provocative for PFE nonsurgical management; on the other, we do believe that in symptomatic patients PFE located in the left heart chambers, the standard of care remains surgical excision after diagnosis. Anyway, our analysis shows that further data in this issue are needed in asymptomatic patients, and surgical indication should be proposed considering carefully the risk-benefit balance.